Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Assgnment 01

Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

ARUSHA TECHNICAL COLLEGE

GSU 07401: ENGINEERING STATISTICS

ASSIGNMENT NO: 02

PARTICIPANTS ADM NUMBER

1. B-10-005
2. B-10-010
3. B-10-015
4. B-10-020
5. B-10-025

PROGRAMME: BACHELOR OF CIVIL AND IRRIGATION ENGINEERING

ISTRUCTORS NAME: MR. S. SLAA

DATE OF SUBMISSION JUNE, 201


QUESTION NO. 1
Two distances are measured as 27.3mm and is 15.6mm with standard deviations of
0.16mm and 0.08mm respectively. Determine the mean and standard deviations of:-
The sum and the difference of the distance
Given:
d1 = 27.3 mm δ = 0.16 mm
d1 = 15.6 mm δ = 0.18 mm

Solution:

µ𝑋𝐴 = 27.3𝑚𝑚

µ𝑋𝐵 = 15.6𝑚𝑚

MEAN OF DIFFERENCES ,
µ𝑋𝐴+ 𝑋𝐵 = µ𝑋𝐴 + µ𝑋𝐵
µ𝑋𝐴+ 𝑋𝐵 = 27.3𝑚𝑚 + 15.6𝑚𝑚
µ𝑿𝑨+ 𝑿𝑩 = 𝟒𝟐. 𝟗𝒎𝒎

𝛿𝑠1+𝑠2 = √𝛿12 + 𝛿22

𝛿𝑠1+𝑠2 = √(0.16)2 + (0.08)2

𝜹𝒔𝟏−𝒔𝟐 = 𝟎. 𝟏𝟖𝒎𝒎

THE DIFFERENCE OF THE DISTANCE


Mean of differences ,
µ𝑋𝐴− 𝑋𝐵 = µ𝑋𝐴 − µ𝑋𝐵
µ𝑋𝐴− 𝑋𝐵 = 27.3𝑚𝑚 − 15.6𝑚𝑚
µ𝑿𝑨− 𝑿𝑩 = 𝟏𝟏. 𝟕𝒎𝒎

𝛿12 𝛿22
𝛿𝑠1−𝑠2 = √ +
𝑁 𝑁

(0.16)2 (0.08)2
𝛿𝑠1−𝑠2 = √ +
1 1
𝜹𝒔𝟏−𝒔𝟐 = 𝟎. 𝟏𝟖𝒎𝒎
QUESTION NO 2:
If P is the observed proportion of successes in a sample of size Ng, show that the
confidence limits for estimating the population proportion of successes “p” at the
level of confidence; determined by Zc are given by:-

𝑍𝑐2 𝑃(1 − 𝑃) 𝑍𝑐2


𝑃 + 2𝑁 ± 𝑍𝑐2 √ +
𝑁 4𝑁 2
𝑝= 2
𝑍
1 + 𝑁𝑐

The formula for the confidence interval for the population proportions p can be
derived as follows
𝑋 − 𝑁𝑝
𝑃 (−𝑍𝑐2 ≤ ≤ 𝑍𝑐2 ) = 1 − 𝛼
√𝑁𝑃(1 − 𝑝)
𝑋−𝑝
𝑃 (−𝑍𝑐2 ≤ 𝑁 ≤ 𝑍𝑐2 ) = 1 − 𝛼
√𝑁𝑃(1 − 𝑝)
𝑁
𝑋
−𝑝
𝑃 −𝑍𝑐2 ≤ 𝑁 ≤ 𝑍𝑐2 = 1 − 𝛼
√𝑁𝑝(1 2− 𝑝)
( 𝑁 )
𝑋
𝐵𝑢𝑡 = 𝑃
𝑁

𝑃−𝑝
𝑃 −𝑍𝑐2 ≤ ≤ 𝑍𝑐2 =1−𝛼
√𝑝(1 − 𝑝)
( 𝑁 )

𝑃−𝑝
𝑃 −𝑍𝑐2 ≤ ≤ 𝑍𝑐2 =1−𝛼
√𝑝(1 − 𝑝)
( 𝑁 )

|𝑃 − 𝑝|
𝑃 ≤ 𝑍𝑐2 =1−𝛼
√𝑝(1 − 𝑝)
( 𝑁 )
(𝑃 − 𝑝)2
𝑃( ≤ 𝑍𝑐2 ) = 1 − 𝛼
𝑝(1 − 𝑝)
𝑁
From:
(𝑃 − 𝑝)2
≤ 𝑍𝑐2
𝑝(1 − 𝑝)
𝑁
𝑝(1 − 𝑝)
(𝑃 − 𝑝)2 ≤ 𝑍𝑐2
𝑁
𝑝 𝑍𝑐2 𝑝2 𝑍𝑐2
𝑃2 − 2𝑃𝑝 + 𝑝2 − + ≤ 0 From this equation the quadratic equation is
𝑁 𝑁
developed.

𝑍𝑐2 2 𝑍𝑐2
(1 + ) 𝑝 − (2𝑃 + ) 𝑝 + 𝑃2 = 0
𝑁 𝑁
From quadratic equation
−𝑏±√𝑏2−4𝑎𝑐
ax2 + bx + c =0 x= 2𝑎
Where
𝑍𝑐2 𝑍𝑐2
x=p a=1 + b=(2𝑃 + ) c=𝑃2
𝑁 𝑁

𝑍 2 𝑍 2 2
𝑍 2
−(2𝑃+ 𝑐 )±√(2𝑃+ 𝑐 ) − 4(1+ 𝑐 )𝑃 2
𝑁 𝑁 𝑁
p= 𝑍 2
2(1+ 𝑐 )
𝑁

𝑍2 𝑍 2 2𝑍 2
2(𝑃+ 𝑐 )±√(2𝑃+ 𝑐 ) −4(1+ 𝑐 )𝑃 2
2𝑁 𝑁 𝑁
p= 𝑍 2
2(1+ 𝑐 )
𝑁

𝑍2 𝑃(1−𝑃) 𝑍2
𝑃+ 𝑐 ± 𝑍𝑐 √ + 𝑐2
2𝑁 𝑁 4𝑁
𝑝= 𝑍2
1+ 𝑐
𝑁
hence the formula shown.

You might also like